Adding whole body vibration to preconditioning exercise increases subsequent on-ice sprint performance in ice-hockey players - Rønnestad, B. R.; Slettaløkken, G.; Ellefsen, S. (The Journal of Strength and Conditioning Research, 2016)
The phenomenon postactivation potentiation can possibly be used to acutely improve sprint performance. The purpose of this study was to investigate the effect of body-loaded half-squats with added whole body vibration (WBV) on subsequent 20 m on-ice sprint performance. Fifteen male ice-hockey players performed 4 test sessions on separate days and in a randomized order. Two of this test sessions were with WBV and 2 were with no WBV and the best sprint time was used to determine effectiveness. Each test session included preconditioning 30 seconds half-squat exercise, 2 of which were supplemented with 50 Hz WBV at a amplitude of 3 mm. One minute after the cessation of the preconditioning exercise, the 20 m sprint test was performed. Intermediate time was sampled after 10 m. Preconditioning exercise performed with 50 Hz WBV resulted in superior 10 m and 20 m sprint performance compared to preconditioning exercise performed without WBV (1.84 ± 0.10 seconds vs. 1.89 ± 0.10 seconds and 3.14 ± 0.13 vs. 3.17 ± 0.13 seconds, respectively, p = 0.01). There was no difference between the protocols in perceived well-being of the legs before the warm-up or after the warm up (p = 0.3). However, there was an improved well-being in the legs immediately after the preconditioning exercise with WBV (p < 0.05). In conclusion, preconditioning exercise performed with WBV at 50 Hz seems to enhance on-ice sprint performance in ice-hockey players. This suggests that coaches can incorporate such exercise into the preparation to specific sprint training to improve the quality of the training.